The role of information security in the development of IT infrastructure and increasing the competitiveness of the university (Journal of Mathematics Mechanics and Computer Science, 2018)
Currently the education sector is developing extremely rapidly, acquiring new features, it’s functional, structural, organizational, ideological and value characteristics are transformed. The dramatic transformation is taking place in higher education. All this creates the problem of finding new sources of increasing the competitiveness of the university. The article is devoted to the role of information security to increase the competitiveness of universities. The level of information security, together with key performance indicators of the work of universities, such as: the quality of the educational process, training of future specialists-graduates, the number and quality of scientific research, highly qualified teaching staff, is an important indicator, since the quality of information security at the university directly affects the reputation and thus its competitiveness. Nowadays, the higher education institutions have not formalized procedures, actions, or measures for the protection of IT infrastructure, there is no a management model of information security.This paper analyzes the main threats to the security of information systems (IS) of higher education institutions, based on the results the management model that can be used as a basis for creating own information security system of universities is proposed. Using this model will effectively prevent and proactively identify threats to information security of IT infrastructure and ensure an appropriate level of information security, one of the indicators of competitiveness of the organization.
Keywords: model of information security provision; IT infrastructure; corporate information system; university; information security